Effect of Different Melatonin-Rich Extract of Emprit Ginger (Zingiber Officinale Var. Amarum) Doses on Biochemical Parameters in Streptozotocin-Induced Diabetic Rats - Tursinawati, Yanuarita; Rosidi, Ali; Hajar, Nabil; Diatri, Devita; Kurniati, Ika Dyah; Rahmatullah, Dyfan Elian; Cleodor, Morita Dascha Winny; Diaz, Pramayshera Erinda Ayuning (Scripta Medica, 2024)
Background/Aim: Emprit ginger (Zingiber officinale var. amarum) is an Indonesian natural plant with various bioactivities, including antidiabetic properties. Several studies have shown that bioactivities can be attributed to the presence of flavonoids and also melatonin which playing a role in carbohydrate metabolism and blood sugar levels regulation. Ginger also has an effect on the lipid profile in studies in experimental animals. Therefore, this study aimed to determine the in vivo antidiabetic activity of melatonin-rich extract of Emprit ginger using blood sugar and lipid profiles parameters. Methods: The study procedure comprised 30 male white rats of Wistar strain, which were divided into 5 groups. These included: I - K-: negative control; II - K+: injected with streptozotocin (STZ) - nicotinamide (NA); III - P1: given STZ-NA + 100 mg/kg body weight (BW)/day ginger extract; IV - P2: given STZ-NA + 200 mg/kg BW/day ginger extract; and V - P3: injected with STZ-NA + metformin 300 mg/kg BW/day. In addition, the treatment was carried out for a total of 21 days, followed by the measurement of random blood sugar (RBS) levels and lipid profiles. Results: The highest pre-treatment RBS, triglyceride, cholesterol, HDL and LDL levels were 426.8 ± 55.8 mg/dL (P2), 142 ± 39.8 mg/dL (P2), 130.8 ± 21.7 mg/dL (K+), 53.4 ± 4.92 mg/dL (P1) and 61.67 ± 17.69 mg/dL (K+), respectively. The results showed that the largest decrease in RBS was obtained in P3 by 262.8 ± 70.6 mg/dL, while P2 experienced the highest decrease in triglyceride levels by 83.66 ± 52.04 mg/dL. In addition, the largest decrease in cholesterol was in P3 by 50.2 ± 26.30 mg/dL, with P1 possessing the highest reduction in HDL by 15.4 ± 15.88 mg/dL. In terms of LDL, the largest decrease was obtained in P3, 20.44 ± 16.68 mg/dL. Based on the results, changes in biochemical parameters levels between all groups showed significant differences except for HDL. Conclusion: STZ-NA injection caused an increase in RBS and cholesterol in rats. Administration of melatonin-rich ginger extract led to a decrease in RBS, cholesterol and LDL and was more effective in the group given metformin. Melatonin-rich ginger extract at a dose of 200 mg/kg BW/day was more effective in reducing triglycerides compared to other clinical parameters.